Late-term development of an atrial defect and thrombus formation after device fracture following successful transcatheter closure of an atrial septal defect with a STARFlex device. (12th December 2016) - Rose, Molly J.; Cevallos, Priscila C.; Gellis, Laura; Bergersen, Lisa
Abstract: Development of a new defect following transcatheter closure of an atrial septal defect has yet to be reported. In this study, we present an acutely successful atrial septal defect closure with a STARFlex device, resulting in surgical explantation after discovery of device fracture, thrombus formation, and a second atrial defect 5 years after catheterisation. This case highlights the need for ongoing device surveillance, even in late follow-up.